Тіотріазолін у комплексному лікуванні хворих з поєднаним перебігом обструктивного апное сну та гастроезофагеальної рефлюксної хвороби - Кривенко, Віталій Іванович; Світлицька, Оксана Анатоліївна; Kryvenko, V.; Svitlytska, O. (Praha: Křižíkova, 2020)
Обстежено 72 пацієнта з коморбідним перебігом обструктивного апное сну (ОАС) та гастроезофагеальної рефлюксної хвороби (ГЕРХ), серед яких 36 хворих отримували антиоксидантну терапію тіотриазоліном 200 мг тричі на добу протягом 3 місяців. Середній вік хворих склав 49,0 (36,0; 59,5) років. У хворих після прийому тіотриазоліну виявилось зниження індексу апное-гіпопное в 1,36 рази, індексу обструктивного апное-гіпопное - в 1,69 рази, мінімальної сатурації – в 1,03 рази, індексу десатурації – в 1,92 рази (р<0,05). Під впливом тіотриазоліну відмічалось зниження сироваткового рівня нітротирозину в 1,43 рази (р<0,05), а рівень 8-оксігуаніну знижувався в 1,30 рази (р<0,05). За даними добового моніторування ЕКГ відмічається зниження напруги вегетативної нервової системи (ВНС), зменшення активності як симпатичної, так і парасимпатичної ланок ВНС в нічний час. Результати СМАТ показали зростання ступеня нічного зниження САТ в 1,82 рази (р<0,05) та АТ сер. в 1,34 рази (р<0,05). На тлі прийому тіотриазоліну відмічалось зменшення індексу «Міокард» в 1,29 рази (р<0,05). Висновки: У пацієнтів з поєднанням ОАС та ГЕРХ на тлі антиоксидантної терапії тіотриазоліном спостерігається зменшення інтенсивності кардіореспіраторних порушень, зниження параметрів оксидативного стресу (нітротирозин, 8-оксігуанін). 72 patients with OSA and GERD comorbid course were examined at the Educational and Scientific Medical Center of ZSMU “University Clinic”, among whom 36 patients received antioxidant therapy with thiotriazoline 200 mg three times a day for 3 months. The mean age of the patients was 49.0 (36.0; 59.5) years. Patients showed a decrease in the apnea-hypopnoe index in 1.36 times, the obstructive apnea-hypopnoe index – in 1.69 times, minimal saturation – in 1.03 times, desaturation index – in 1.92 times (p<0.05) after receiving thiotriazoline. Under the influence of thiotriazoline, there was a decrease in serum nitrotyrosine level in 1.43 times (p<0.05), and the level of 8-hydroxyguanine decreased in 1.30 times (p<0.05). According to daily ECG monitoring, there is a decrease in autonomic nervous system voltage, a decrease in activity of both sympathetic and parasympathetic nervous system units in the night-time. The daily blood pressure monitoring results showed an increase in the nocturnal reduction rate of systolic blood pressure (BP) by 1.82 times (p<0.05) and middle BP by 1.34 times (p<0.05). On the background of receiving thiotriazoline, a decrease in the Myocardium index was observed in 1.29 times (p<0.05). Conclusions: In patients with combination of OAS and GERD on the background of the antioxidant therapy with thiotriazoline there is a decrease in the intensity of cardiorespiratory disorders, a decrease in the oxidative stress parameters (nitrotyrosine, 8-oxyguanine).
Thiotriazoline in the complex treatment of patients with obstructive sleep apnеа and gastroesophageal reflux disease comorbid flow
Keywords: обструктивне апное сну; гастроезофагеальна рефлюксна хвороба; кардіореспіраторні порушення; нітротирозин; 8-оксігуанін; obstructive sleep apnea; gastroesophageal reflux disease; cardiorespiratory disabilities; nitrоtyrosine; 8-oxyguanine